Quality of service (QoS) based recovery scheme in MPLS network - AbdHood Hanshi, Sabri Mohammed (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
With the explosive growth in the quality of service (QoS) traffic on the Internet, multi- protocol label switching (MPLS) plays a key role by delivering QoS and traffic engineering in next generation Internet by supporting the requirements of real time application. Link failure incurs delay and packet losses in the main path in addition to compromise the availability of the system. In MPLS, fast reroute has attracted a lot of attention by computing and signalling backup label switched path (LSP) tunnels in advance, in order to meet fast restoration of protected traffic in case of failure. However, real time application for example, requires additional parameters to be guaranteed in the recovery scheme such as bandwidth, latency and jitter. In this thesis, a new QoS protection in the MPLS network has been proposed to support quality of service of protected traffic in case of failure. This research introduces four procedures in order to guarantee QoS requirements for the protected traffic. (i) the ingress node establishes more than one alternative path in advance to provide fast recovery and reliable rerouting. (ii) Collecting and calculating all network information needed the alternative path selection. (iii)Two selection criteria are introduced proposed scheme which are used are bandwidth availability and end-to-end delay in each alternative path in order to guarantee the QoS requirements for the protected traffic after failure take place. In case of insufficient resources in the alternative paths individually to deliver the traffic, a traffic splitter has been proposed to split the protected traffic among the available alternative paths. (iv) Alternative path selection is updated according to current state of network resource availability. To verify the efficiency of the proposed algorithm, the MPLS network simulator (MNSv2) has been used as experimental platform. Two different scenarios are evaluated as well as one scenario to compare the proposed scheme with existing scheme called fast reroute with pre-established by pass tunnel (BPT). The results of the simulation show that the proposed scheme can ensure that required bandwidth for protected traffic in case of failure at different cases of available capacity in alternative paths. In term of packet loss the proposed scheme introduces 60% better than BPT. In term of throughput of protected traffic at the receiving point the proposed model has better result than BPT, because the proposed scheme is adaptive the current status of network resource availability.